Effects of meteorological factors and groundwater depths on sap flow density of Populus euphratica in a desert oasis, Taklamakan Desert, China - Wan, Yanbo; Peng, Lei; Anwaier, Abudureyimu; Shi, Haobo; Li, Dinghao; Ma, Yu; Shi, Qingdong (Frontiers in Plant Science, 2024)
Accurate estimation of desert vegetation transpiration is key to regulating desert water resources of desert ecosystems. Sap flow density (SFD) can indirectly reflect a tree's transpiration consumption, and it has been affected by climate warming and groundwater depths in desert ecosystems. Sap flow responses to meteorological conditions and groundwater depths are further affected by tree of different sizes.However, how meteorological factors and groundwater depths affects tree sap flow among tree sizes remains poorly understand. In this study, a 50 × 50 m P. euphratica stand was selected as a sample plot in the hinterland of the Taklamakan Desert, and the SFD of P. euphratica of different sizes was measured continuously using the thermal diffusion technique from May to October of 2021 and 2022. The results showed that SFD of large P. euphratica was consistently higher than that of small P. euphratica in 2021 and 2022. and the SFD of P. euphratica was significantly and positively correlated with solar radiation (Rad) and vapor pressure deficit (VPD), and the correlation was higher than that of the air temperature (Ta) and relative humidity (RH), and also showed a strong non-linear relationship. Analysis of the hour-by-hour relationship between P. euphratica SFD and VPD and Rad showed a strong hysteresis. Throughout the growing season, there was no significant relationship between SFD of P. euphratica and groundwater depth, VPD and Rad were still the main controlling factors of SFD in different groundwater depths. However, during the period of relative groundwater deficit, the effect of groundwater depth on the SFD of P. euphratica increased, and the small P. euphratica was more sensitive, indicating that the small P. euphratica was more susceptible to groundwater changes. This study emphasized that Rad and VPD were the main drivers of SFD during the growing season, as well as differences in the response of different sizes of P. euphratica to groundwater changes. The results of the study provide a scientific basis for future modeling of transpiration consumption in P. euphratica forests in desert oases, as well as the regulation and allocation of water resources.